IMPLEMENTASI PEMBIAYAAN SERTIFIKASI GURU (SERGU) PADA PT.BPRS KABUPATEN NGAWI (PERSERODA) KANTOR KAS PARON - Suprihatin, Sholikah; Linawati, Linawati (Investama : Jurnal Ekonomi dan Bisnis, 2024)
Financing is the process of providing funds or capital given by one party to another party to support a planned investment. Teacher Certification Financing (SERGU) is a financial facility provided by financial institutions, such as BPRS (Sharia People's Credit Bank) to teachers who already have a teacher certificate. This study aims to analyze the mechanism of implementing teacher certification financing at BPRS Ngawi Regency using the murabahah contract, and its effect on teacher welfare. The type of research is qualitative or field research. Data collection methods through interviews and documentation. From the results of this study, it can be seen that the implementation of teacher certification financing (SERGU) at PT. BPRS Ngawi Regency (PERSERODA) Paron Cash Office has been running effectively, but there are still several obstacles that need to be overcome. Teacher Certification Financing (SERGU) has a positive impact on improving teacher welfare, especially in meeting financial needs such as consumption, investment, and education.